Pelayanan Jasa Keagenan dalam Menunjang Kelancaran Clearance in dan Clearance Out di PT. Karya Lautan Sriwijaya - Syafriyansyah Syafriyansyah; Miko Dwi Agostian; Muhammad Syukri (Lembaga Pengembangan Kinerja Dosen, 2025)
This research aims to examine agency services in supporting the smooth clearance in and clearance out process at PT Karya Lautan Sriwijaya Palembang. The research method used is a descriptive qualitative approach with data collection techniques through observation, interviews, and literature studies. The results of the study show that ship agency services have been carried out in accordance with applicable procedures, including the management of ship documents and coordination with related agencies such as KSOP and KKP. In addition, ship agents also play a role in ensuring the smooth administration of ship arrivals and departures, including the fulfillment of shipping safety and health requirements. However, the study found several obstacles that hinder service optimization, such as delays in signing documents, limited dock availability, network disruptions in digital systems, and delays in cargo readiness from related parties. The non-uniform communication factor between agencies is also a challenge. Overall, agency services at PT Karya Lautan Sriwijaya have been running quite effectively, but there is still a need to improve cross-agency coordination, accelerate bureaucratic processes, and optimize supporting infrastructure to improve service quality in a sustainable manner.